Disruption of Oil Palm Empty Fruit Bunches by Microwave-assisted Oxalic Acid Pretreatment - Nissa Nurfajrin Solihat; Fahriya Puspita Sari; Lucky Risanto; Sita Heris Anita; Fitria Fitria; Widya Fatriasari; Euis Hermiati (Journal of Mathematical and Fundamental Sciences, 2017)
Developing an effective pretreatment for the conversion of lignocellulosic biomass to ethanol is an important effort in reducing the cost of this process. Microwave-assisted pretreatment is considered a green technology that can effectively break down lignocellulosic structures. The objective of this study was to investigate the most effective temperature for microwave-assisted oxalic acid pretreatment regarding the structural characteristic changes of oil palm empty fruit bunches (OPEFB) fibers. The fibers were subjected to microwave-assisted oxalic acid pretreatment at 160"“200 °C with 2.5 minutes heating time and a liquid to solid ratio of 10. The effectiveness of the pretreatment was determined based on its delignification selectivity, morphological characteristics, and functional group changes. Microwave irradiation of OPEFB fibers at 180 ºC was effective in increasing the cellulose content by 24%. This pretreatment resulted in 1.82 delignification selectivity. More than 50% of the hemicellulose of the OPEFB was removed after this treatment, which was confirmed by a decrease of the absorption bands of functional groups at 1732 cm-1. The increase of pretreatment temperature disrupted the morphological structure of the OPEFB and removed its hemicellulose but did not change its functional groups and lignin content.